Creative Process in Psychotherapy: Form and Structure as A Basis of Treatment - Rothenberg, Albert (International Journal of Psychotherapy Practice and Research, 2025)
This conceptual paper proposes that form and structure in the creative process provide a basis for psychotherapy interventions. It illustrates how framing, pattern, and iteration can support change within different modalities.
Keywords: Creativity; Form and Structure; Interpersonal Relationship; Artistic Structure; Original Research